Religious Attendance and Cancer Screening Behavior - Kretzler, Benedikt; König, Hans-Helmut; Hajek, André (Frontiers in Oncology, 2020)
Background: Cancer is one of the most important health problems worldwide. Preventive examinations proved to be effective in tackling that issue, but their degree of utilization is not adequate. Thus, research is making efforts to reveal its determinants. It has been shown that religion is associated with several health outcomes, so the aim of our study is to analyze the association between religious attendance and participation in cancer prevention. Methods: Data are derived from the fifth wave of the German Aging Survey (DEAS), a nationally representative, prospective cohort study. Participants are community-dwelling Germans aged 40 years and older. Our main independent variable is the frequency of attendance in religious services, and the dependent variable is participation in cancer screening. As covariates, we include factors from all the dimensions of the Andersen behavioral health services utilization model. Multiple logistic regressions were used. In our sensitivity analysis, logistic regressions were performed stratified by religious group (Roman Catholic church, Protestant church, not belonging to any religious group). Results: Our model shows that attendance in religious services once a week, one to three times a month, several times a year, or less often is significantly associated with an increased likelihood of participating in preventive cancer screening, more than never participating in religious services. Moreover, the sensitivity analysis reveals that all these associations remain significant for the Catholic subsample, but not for the Protestant or the non-religious group. Discussion: This study finds a link between a higher frequency of attendance in religious services and an increased likelihood of participating in cancer screenings. This is important to address individuals at risk for underuse of cancer screenings.